Historigraphical balance and cientific contributions of the Bicentennial of the napoleonic occupation in Navarra, Aragón, Álava and La Rioja - Miranda Rubio, Francisco (Huarte de San Juan. Geografía e Historia, 2016)
The bicentenary of the Independence War has lead to a scientific production of great interest and to several congresses, conferences and cultural activities of various kinds. The most discussed topics in the Congresses of Navarra, Aragón, Álava and La Rioja were the moment of the appearance of the concept of nation, the historical memory as subjective construction of the past and the public uses of history because of the instrumentalization of the past from political positions as well as from the public institutions.